Women and the freedom of reinterpreting the holy text: a study of sisters in Islam and their interpretation of Qur’an verses and hadith on marital issue - Muhamad Shukri, Abdul Salam; Owoyemi, Yusuf Musa (2015)
The article discusses the reinterpretation effort of the Muslim feminist movement in Malaysia, Sisters in Islam (SIS). The article looks at the effort of the group in reinterpreting some verses of the Qur'an and hadiths on the issue of women in marital relationship by Muslim male exegetes. Using the text analysis method, this article examines some works written and commissioned by the association and its authors on this issue. In four sections, the article explores four works of the association on the following issues, namely (i) Are Muslim men allowed to beat their wives?, (ii) Guardianship law and Muslim women, (iii) hadith on women in marriage, and (iv) Islam and family planning or Muslim women's reproductive rights. While the first and second parts discuss the issue of wife beating and guardianship law and Muslim women, the third and fourth parts examine hadith on women in marriage and Islam and family planning. Through its analysis of these works, the article concludes on the note that these were mostly influenced by the works of Muslim feminist scholars such as Amina Wadud and Fatima Mernissi and as such contain controversial reinterpretation of the verses of the Qur'an and habits.